Changes in hormone receptors and proliferation markers in tamoxifen treated breast cancer patients and the relationship with response - Makris, A.; Powles, T.J.; Allred, D.C.; Ashley, S.; Ormerod, M.G.; Titley, J.C.; Dowsett, M. (Breast cancer research and treatment, 1998)
To determine the effects of tamoxifen on the levels of hormone receptors and proliferation markers in the early phase of treatment and the relationship of the changes with tumor response in patients with primary breast cancer. Twenty-one women with primary, operable breast carcinomas were treated with tamoxifen 20 mg daily. Fine needle aspiration (FNA) was used to obtain samples prior to the start and at 14 days and 8-weeks post-treatment. From these samples estrogen receptor (ER), progesterone receptor (PgR), and Ki67 levels were determined using immunocytochemistry and ploidy and S-phase fraction (SPF) using flow cytometry. Tumor response was measured clinically according to UICC criteria. There were 12 responders (2 CR, 10 PR) and 9 non-responders (2 NC, 7 PD). Responders were more likely to be ER+ (p = 0.002), PgR+ (p = 0.006), and low SPF (p = 0.06). At 14 days post-tamoxifen, the median decrease in Ki67 (% cells staining) for responders was -4.8 and for non-responders -0.15 (p = 0.005). This decrease was seen predominantly in ER+ tumours. The difference in SPF was not significant. A decrease in ER was seen in 3/15 patients all of whom were responders. A rise in PgR was seen in 7/17 patients and all but one were responders. Similar changes for ER and PgR were seen at 8-weeks post-tamoxifen, although the reductions in Ki67 and SPF at that time point were not related to response. We have observed a decrease in Ki67 and ER and a rise in PgR after 14 days of treatment with tamoxifen that was related to subsequent response. This is the first study in which an early decrease in a proliferation marker has been shown to relate to subsequent clinical response.